Peso, trabalho e direito: gordofobia e direito antidiscriminatório trabalhista - Isabella Filgueiras Gomes (2024)
This study addresses fatphobia and Anti-Discrimination Employment Law. It aims to analyze how – in terms of enactments by the Legislature, provocation and action by the Labor Prosecution Office and the Labor & Employment Court – the social stigmatization of fat people affects the way discrimination is legally dealt with in the workplace. To this end, the thesis is divided into five sections. The first section examines the changes in the image of fat people throughout history, the medical pathologization of “obesity”, the emergence of fat activism, and the positioning of fat people in applied social sciences, especially Law. The second section provides a conceptual analysis of stigma, discrimination, and fatphobia, followed by a concrete examination of the ways in which fatphobia is expressed in various social realms. The third section analyzes the phenomenon of fatphobia in the workplace, throughout the pre-hiring, hiring, and dismissal stages. The fourth section looks at the concept of Anti-Discrimination Law, its foundations and structure, and positions the fat worker and the employer as subjects of anti-discrimination rights and obligations, respectively. The fifth section breaks down the legal and labor approaches to fatphobia, both at the international and national levels. The study, which is grounded in a legal-comprehensive approach, brings a bibliographical review; a review of the International Labor Organization Conventions; the 1988 Constitution of the Federative Republic of Brazil; federal, state and local laws; research of case law, especially from the Superior Labor Court and the Regional Labor Courts; and research on lawsuits and extrajudicial proceedings of the Labor Prosecutor's Office. It concludes that the stigmatization of fat people, peculiarly characterized by fat shaming and by the moralizing invocation of health discourses, leads to a pronounced social tolerance of discriminatory situations, with various repercussions on the legal-labor approach to the issue. After reviewing progress and challenges, some anti-discrimination proposals are formulated.